Stringlish: improved English string searching in binary files. (8th April 2015) - Aycock, J.
Summary When analyzing binary files, printable strings are easy to find, but a naïve approach yields a large number of false positives: 'uninteresting' string‐like sequences that occur by chance in the binary. We present a lightweight yet surprisingly effective method of filtering printable strings for English or English‐like sequences. Copyright © 2015 John Wiley & Sons Ltd.